Primer Informe de Lutzomyia Franca en el Departamento de Guainía, Amazonia Colombiana, y de Brumptomyia mesai Sherlock (Diptera: Psychodidae) en el Litoral Caribe Colombiano (2007)
ABSTRACT - This is the fi rst record of the presence of the medically important genus Lutzomyia França in the Department of Guainía, Colombia. Sand fl ies were collected biting humans in the surroundings of the urban area of the Municipality of Inírida. Three Lutzomyia species were taxonomically identifi ed as L. davisi (Root), L. olmeca bicolor Fairchild & Theodor, and L. antunesi (Coutinho). Additionally, Brumptomyia mesai Sherlock is cited for the fi rst time in the Caribbean Coast of Colombia based on specimens collected with a modifi ed CDC light trap in the Reserva Forestal Protectora Serranía de Coraza y Montes de María, Department of Sucre